Social Commerce Adoption to Enhance SMEs Performance: Technology, Organization and Environment (TOE) Perspectives - Lina, Lia Febria; Suwarni, Emi (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
Currently, the shift in consumer behavior has led to an increase in the average value of purchase transactions. This is an opportunity for SMEs to take advantage of the digital space for business acceleration. This study aims to explore the technological, organizational, and environmental (TOE) framework as a driving factor technological adoption. Technological factors used in this study are the benefits obtained and utilized. Then, the organizational factors tested in this study are top management support and knowledge of IT/IS employees and the last environmental factor is customer pressure and competitive pressure. This study uses a quantitative approach and survey methods to 144 SMEs. The findings in this study are perceived advantage, top management support and customer pressure have positive effect on technology adoption and have an effect on SMEs performance both on financial performance and brand performance. Keywords: SMEs, social commerce, technological, organization and environmental (TOE)